Effects of echo time on IVIM quantifications of locally advanced breast cancer in clinical diffusion‐weighted MRI at 3 T. (30th December 2021) - Egnell, Liv; Jerome, Neil P.; Andreassen, Maren M. S.; Bathen, Tone F.; Goa, Pål Erik
Abstract : Purpose: The purpose of this study was to investigate the effects of echo time dependence in IVIM quantification of the pseudo‐diffusion fraction in breast cancer and whether correcting for the echo time dependence offers added clinical value. Materials and methods: Fifteen patients with biopsy‐proven breast cancer underwent a 3 T MRI examination with an extended DWI protocol at two different echo times ( TE = 53 ms, b = 0, 50 s/mm 2 ; TE = 77 ms, b = 0, 50, 120, 200, 400, 700 s/mm 2 ). Volumes of interest were delineated around the tumors. In addition, simulated MRI data were generated for different levels of signal‐to‐noise ratio and two values for the blood T2 relaxation time ( T2 p = 100 ms and 150 ms). The pseudo‐diffusion signal fraction was estimated from the simulated and in vivo tumor data using both the standard IVIM model and an extended IVIM model that accounts for the echo time dependence arising from distinct transverse relaxation times. Results: Simulations showed that the standard IVIM model overestimated the pseudo‐diffusion fraction by 25% ( T2 p = 100 ms) and 60 % ( T2 p = 150 ms) ( p  < 0.0001 at SNR = 50). In vivo, the estimated apparent T2 value at b = 50 s/mm 2 was around 8% lower than at b = 0 s/mm 2 ( p = 0.01) demonstrating a removal of the signal contribution from blood with long T2 associated with pseudo‐diffusion. Using two different fixed values for T2 p = 100, 150 ms, the pseudo‐diffusion fraction was 15% and 46% higher in the standard model compared with the echo‐time‐corrected model ( p  < 0.01). Conclusion: The standard IVIM model was found to overestimate the pseudo‐diffusion fraction by 15% to 46% compared with the echo‐time‐corrected model in breast tumor DWI data acquired at 3 T. Our results suggest that a corrected model may give more accurate results in terms of signal fractions, but may not justify the added time needed to acquire the additional data in terms of clinical value.